Dental Image Analysis for Disease Diagnosis - Jain, Kavindra R.; Chauhan, N. C. (Springer International Publishing : Imprint: Springer, 2019)
This book provides an overview of computational approaches to medical image examination and analysis in oral radiology utilizing dental radiograph to detect and diagnose dental caries in cases of decayed teeth. Coverage includes basic image processing techniques; approaches for Region of Interest extraction and analysis; and the role of computational clustering techniques for segmentation of teeth and dental caries. The book also presents a novel multiphase level set method for automatic segmentation of dental radiographs.